End milling finite element method for cutting force prediction and material removal analysis - Suraidah, S.; Muhamad Ridzuwan, .; Gebremariam, M. A.; Azmir, Azhari; Kassa, Freselam Mulubrhan (IOP Publishing, 2020)
The paper presents an orthogonal cutting finite element model analysis on Aluminum 6061 in order to investigate the effect of different number of cutting tool flutes (two and four) on the von misses stress distribution and analysis of cutting forces in three force direction which are in Fx,Fy,Fz. The machining parameters used in the simulation and experiment was a depth of cut of 3 mm and 6 mm with a recommended machining parameter, a 2-flute and 4-flute end mill cutter used for each case. The results showed that the simulation and experiment indicated that the predicted and the measured cutting force of milling process are in a good agreement and the shape of the chip generated was similar.